Pengaruh Budaya Kerja dan Beban Kerja Terhadap Kinerja Karyawan Pada Bank Syariah Indonesia KC Depok Margonda 2 - Pradiva Priski Saputri; Nurlaela Eva Puji Lestari; Sudirja Sudirja (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The analysis intends to evaluate the impact of company values also workload on staff performance at Bank Syariah Indonesia KC Depok Margonda 2. Utilizing a quantitative statistical method, data collection involves observations and surveys provided to 33 employees. Using SPSS version 27, data assessment included aNOVA, correlation analysis, chi-square test, and R-squared value. Outcomes from the t-test reveal workplace culture (X1) adversely affects employee output (Y), yielding a t-value of -5.266, greater t-table 1.697 a significance value of 0.000. In conclusion, workload (X2) contributes positively and considerably to performance, reflected by a t-value of 5.765 > t-table 1.697 also a significance of 0.000. The F-test confirms that both variables jointly affect performance significantly (F-value 16.700 > F-table 3.316). The coefficient of determination (R²) measures 52.7%, revealing that work culture and workload together affect performance, with the remaining 47.3% influenced by different variables.